On the observed response of ozone to NOx and VOC reactivity reductions in San Joaquin Valley California 1995–present - S. E. Pusede (Atmospheric Chemistry and Physics, 2012)
We describe the effects of nitrogen oxide (NOx) and organic reactivity reductions on the frequency of high ozone days in California's San Joaquin Valley. We use sixteen years of observations of ozone, nitrogen oxides, and temperature at sites upwind, within, and downwind of three cities to assess the probability of exceeding the California 8-h average ozone standard of 70.4 ppb at each location. The comprehensive data records in the region and the steep decreases in emissions over the last decade are sufficient to constrain the relative import of NOx and organic reactivity reductions on the frequency of violations. We show that high ozone has a large component that is due to local production, as the probability of exceeding the state standard is lowest for each city at the upwind site, increases in the city center, is highest at downwind locations, and then decreases at the receptor city to the south. We see that reductions in organic reactivity have been very effective in the central and northern regions of the San Joaquin but less so in the southern portion of the Valley. We find evidence for two distinct categories of reactivity sources: one source that has decreased and dominates at moderate temperatures, and a second source that dominates at high temperatures, particularly in the southern San Joaquin, and has not changed over the last twelve years. We show that NOx reductions are already effective or are poised to become so in the southern and central Valley, where violations are most frequent, as conditions in these regions have or are transitioning to NOx-limited chemistry when temperatures are hottest and high ozone most probable.